Evaluasi Pengambilan Keputusan berbasis Resiko dalam Manajemen Proyek - Citra Yasmin; M. Chaerul Rizky; Mouza Hasanah; Dewi Jelita; Jauzaa Fadhiilah; Nabila Sahda Marcella (Jurnal Simki Economic, 2026)
The contemporary business environment characterized by volatility, uncertainty, complexity, and ambiguity (VUCA) demands a proactive approach to project management. This study aims to evaluate the effectiveness of implementing risk-based controls in project management, with a particular focus on the interaction between structural frameworks and behavioral factors influencing risk-taking and decision-making. A systematic literature review with a qualitative approach was used to synthesize theoretical and empirical findings. The analysis revealed that the gap between risk management principles and practices, as reported in global studies, is significantly influenced by systematic cognitive biases such as loss aversion and the framing effect. These biases distort risk assessments, trigger inertia in problematic projects, and lead to suboptimal allocation of control resources. The study concludes that the effectiveness of risk-based controls cannot be achieved solely through adherence to procedural frameworks such as ISO 31000.